Synergizing Thematic Qur’anic Exegesis and Legal Regulation: Reconstructing Qur’anic Values to Prevent Child Marriage in Indonesia - Mukhtar Yunus (Program Pascasarjana UIN Sumatera Utara, 2023)
Although Law No. 16 of 2019 concerning the Amendment to Law No. 1 of 1974 on Marriage has raised the minimum legal age of marriage to 19 years for both men and women, child marriage remains a pressing social phenomenon in Indonesia. Beyond its legal dimension, this issue also contains theological aspects that require the reconstruction of religious understanding. This article examines how legal regulation and thematic Qur’anic interpretation can work together to prevent child marriage in Indonesia. Using a qualitative research method with document analysis and literature study approaches, this study argues that the reconstruction of Qur’anic values through thematic interpretation, particularly concerning the concepts of bulūgh (maturity), rushd (responsibility), and maṣlaḥah (public benefit), can provide a theological foundation for strengthening regulations against child marriage. As a result of this synergy, Islamic law is understood not merely as requiring biological age, but also as emphasizing psychological, emotional, and socio-economic maturity that can be objectively measured for a marriage to be considered valid and beneficial. These findings have practical implications for the formulation of child protection measures in Indonesia and offer an academic contribution to the development of contextual Islamic jurisprudence.